Development of designing and fabricating a compact drying machine / Muhammad Hazrin Amri Mohd Hariri - Mohd Hariri, Muhammad Hazrin Amri (2024)
Since the clothes dryer machine enters the market in Malaysia, only a few people are convinced that it is important in our daily life. The disbelief comes from a few different factors. These factors include the high prices of the machine, the importability of the machine and the high energy consumption of the machine. Thus, this project is done with the objective of designing and fabricating a machine that is not also small, energy efficient, portable, and inexpensive. This machine is aimed towards student and unmarried people that cannot afford a real clothes dryer machine and only need a small amount of load. The machine is designed with the help of the software SOLIDWORKS 2021 and is fabricated with machining processes. The material used also needs to be cheap, light, and durable. The outcome that the machine is able to achieve the objectives stated being smaller than the market designs, portable and cheap to make. The machine is also able to remove moisture from clothing in a short time.